Avaliação da temperatura de secagem e do armazenamento na composição química e qualidade sensorial do tomate seco - Cruz, Patricia Moretti Franco da (2011)
The objective of this study was to evaluate the effect of drying temperature and storage time on the physical, chemical and sensory quality of dried tomatoes. The drying temperature of the tomato 'Dominador' were: 55 ºC, 65 ºC, 75 ºC and 85 ºC. The storage under refrigeration at 5 º C ± 2 ºC was carried out only with sun-dried tomatoes at a temperature of 75 °C, measured on day 1, 15, 30, 45, 60, 75 and 90. In both tests, we used a completely randomized design with five replicates and the results, analysis of variance. The mean comparison test of Tukey (p <0.05) and regression analysis were applied to the results of drying and storage, respectively. The drying temperature had an effect on the physical, chemical, and sensory quality of the tomato, where the increase in drying temperature provided acidity and decrease in the levels of ascorbic acid and beta-carotene and increase in the levels of total phenolics and lycopene. There was increased red color and darkening in the sun dried tomatoes with increasing drying temperature. According to sensory analysis, among the tested temperatures in drying tomatoes presented the best results at 75 °C. Throughout the storage process th ere was a loss in content of ascorbic acid, total phenolics, lycopene and beta carotene. As for the analysis of color, darkening of the sun dried tomatoes occurred, regardless of the position of tomatoes assessed. Losses occurred during storage of nutritional quality of dried tomato, in this case, which did not include any type of preservative, the product should be consumed as soon as possible